KAJIAN FAKTOR PENENTU MASA SIMPAN PRODUK BUBUK BUMBU DENGAN CARRIER MALTODEKSTRIN DE-12 DAN DE-18 - Widjajaseputra, Anna Ingani; Srianta, Ignatius; Handayani, Yashinta Natalia (Jurnal Teknologi Pangan dan Gizi, 2003)
Seasoning powder is very useful in modern life. Seasoning powder can make certain food preparation easier, such as fried chicken, fried shrimp etc. The problem are discoloration and free flowing ability due to the increasing of reducing sugar content during storage. The objective of this research is to study on dominant factors of shelf-life of seasoning powder using maltodextrine, DE-12 and DE-18 as "carrier". A Complete Randomized Design has been used, with two levels of Dextrose Equivalent of maltodextrin, DE-12 and DE-18, respectively. Measured parameters are moisture content, water activity, reducing sugar content, free flowing and color. All data from five replicates were analyzed statistically using t test and set at Pd" 0.05. The research result indicate that the dominant factors of shelf-life are free flowing and color. Seasoning powder using DE-12 has 6 weeks shelf-life and the other one using DE-18 has 4 weeks shelf-life.